IMPLEMENTASI NILAI KARAKTER RELIGIUS DAN IMPLIKASINYA TERHADAP KEDISIPLINAN SISWA DI SMK SYAMSUL ARIFIN PUKUL KRATON PASURUAN - Siti Aisyah; Muhammad Khoirul Lutfi (Universitas Nahdlatul Ulama Pasuruan, 2023)
Character education plays a pivotal role in molding individuals to uphold and respect established norms and regulations. At SMK Syamsul Arifin Pukul Kraton Pasuruan, student discipline is cultivated through the integration of religious character values. This integration is reinforced by activities such as pre-learning tahfidz sessions, communal Dhuhr prayers, and monthly grave visits. The objective of this study is to delineate the planning process of religious character values, their practical implementation, and the subsequent impact on student discipline at SMK Syamsul Arifin Kraton Pasuruan. This research adopts a qualitative methodology. Qualitative research is an investigative approach that transcends mere statistical analyses and quantification. The study is primarily descriptive in nature, conducted directly by the researcher. The research findings reveal that: 1) The incorporation of religious character values is manifested through synchronized tahfidz sessions at the outset of learning, as well as voluntary tahfidz sessions for interested students. Additionally, collective Dhuhr prayers and monthly grave visits are observed every Friday. 2) Regarding the ramifications of instilling religious character values, students exhibit enhanced proficiency in time management, thereby fostering a more disciplined demeanor among them.